A Feasible SQP Method Using Augmented Lagrangian Function for General Constrained Optimization - Xiaowei Jiang; Yueting Yang; Yunlong Lu (2012 Fifth International Joint Conference on Computational Sciences and Optimization, 2012)
An feasible SQP method is proposed to solve general optimization problems with equality and inequality constraints. First, we transform the original problem to an associated simpler problem with only inequality constraints, and the simplified problem is shown to be equivalent to the original problem under the mild condition. Then we use feasible SQP method to solve the latter problem. Here, we use the augmented Lagrangian function to be objective function. At each iteration, multiplier and penalty parameter are updated by the simpler criterion. Numerical experiments are implemented to test the efficiency of the proposed method.